Comprehensive analysis of the long noncoding RNA expression profile and construction of the lncRNA-mRNA co-expression network in colorectal cancer. Issue 2 (1st February 2020) - Zhang, Qun; Ding, Zhou; Wan, Li; Tong, Wenyu; Mao, Jialei; Li, Li; Hu, Jing; Yang, Mi; Liu, Baorui; Qian, Xiaoping
ABSTRACT: Long noncoding RNAs (lncRNAs) have been shown to play important roles in various tumors including colorectal cancer (CRC). Here, we obtained data from RNA-sequencing analysis using 3 paired of CRC tissues and corresponding normal tissues. Through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, the biological functions of these dysregulated genes were identified. Moreover, we analyzed the expression levels of lncRNA PGM5-AS1 and B3GALT5-AS1 by quantitative real-time PCR (qRT-PCR) assay. To evaluate the accuracy of the lncRNA-mRNA co-expression network we built, we also detected PGM5 expression and analyzed the relationship between PGM5-AS1 and PGM5 in CRC. In addition, we explored the potential function of PGM5-AS1 in vitro and in vivo. In conclusion, we identified dysregulated lncRNAs and constructed the lncRNA-mRNA co-expression network in CRC. Then, we showed that the expression levels of PGM5-AS1, B3GALT5-AS1 and PGM5 were significantly downregulated in CRC tissues compared with corresponding normal tissues. Besides, PGM5-AS1 expression was positively associated with PGM5 expression. These findings were consistent with our RNA-sequencing data. Functionally, overexpression of PGM5-AS1 could induce cell apoptosis and cell cycle arrest in CRC. Animal study indicated that PGM5-AS1 overexpression inhibited CRC growth in vivo. This work provides dysregulated lncRNAs as candidates for further study in CRC. The lncRNA-mRNA co-expression network brings novel insights into further function research. More importantly, PGM5-AS1 is a critical tumor suppressor in CRC.